Effect of Chitosan as a Biological Sanitizer for Salmonella Typhimurium and Aerobic Gram Negative Spoilage Bacteria Present on Chicken Skin - Menconi, Anita; Hernandez-Velasco, Xochitl; Latorre, Juan David; Kallapura, Gopala; Pumford, Neil R.; Morgan, Marion J.; Hargis, B.M.; Tellez , G. (International Journal of Poultry Science, 2013)
Two experiments were conducted to evaluate the effect of chitosan as a biological sanitizer on chicken skin during storage. For experiment 1 (two trials) five skin samples of equal size were dipped into a solution containing 106 cfu/mL of Salmonella Typhimurium (ST) for 30s. Skin samples were then removed and dipped into a solution containing PBS or 0.5% chitosan for 30s. In experiment 2, aerobic Gram negative spoilage bacteria were used as indicators instead of ST. In both experiments, all samples were placed in individual bags and kept at 4°C. In experiment 1, dipping ST contaminated skin samples in a solution of 0.5% chitosan reduced (p<0.05) the recovery of ST by 24 h. In experiment 2, 0.5% chitosan treatment solution reduced (p<0.05) the presence of spoilage-causing psychrotrophic bacteria below detectable levels. These results suggest that 0.5% chitosan has a potential for use in an intervention technology for the control of foodborne pathogens on the surface of chicken skin contaminated with bacteria during storage.